“The ways of soul, mind and heart to God — no one can intercept them...”: Letters of hegumen Amfilokhiy of Konev to prince A. V. Obolensky, 1926–1934 - Tatyana Shevchenko (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The publication covers 21 letters by the father-superior of the Konevsky Nativity of the Theotokos Monastery in Finland, hegumen Amphilochius (Kulakov) to the emigrant of the first wave, Prince Alexei Vasilyevich Obolensky in the period 1926-1934. The letters were kept in the archive of the New-Valamo Monastery in Finland and are published for the first time. The first of the submitted letters was written by hegumen Amphilochius on June 23, 1926, the last - on January 27, 1934. Until 1939, the hegumen still congratulated the Obolenskys on Christmas and Easter. The correspondence began when the hegumen was 51 years old, for eight years he wrote about 2-3 letters annually, and after 1934 he sent brief congratulations on church celebrations. Father Amphilochius took monastic vows in the Valaam Monastery in 1908, and in 1920 was moved to the Konevsky Monastery. He became one of the brightest representatives of the old-style movement. It arose after the Finnish Orthodox Church introduced the Gregorian calendar (1921) and the "new" Paschal in 1925. A Church court condemned him and removed from the abbacy for refusing to accept the reform. Nevertheless, the former father-superior remained to live in the monastery, performed general monastic work and prayed in a cell. His correspondence with Obolensky was mainly of a spiritual upbringing nature, however, some references concerned to the church life of that time. The letters are also interesting because of revealing of the inner world and views of one of the "leaders" of the old-style movement in Finland, they show him as a deeply spiritual person devoted to monastic traditions.